EXPLORING ESCAPISM AND STRUGGLE FOR EXISTENCE IN EXIT WEST BY MOHSIN HAMID: A POSTCOLONIAL PERSPECTIVE - Muhammad Iqbal; Misbah Bashir; Khalida Parveen (International Journal of Contemporary Issues in Social Sciences, 2024)
The current study seeks to acquire a deeper understanding of the significant elements of escapism and identity crises within post-colonial diasporic contexts, explicitly focusing on the novel Exit West by Mohsin Hamid. The researcher endeavours to employ a comparative methodology utilizing the influential work of Edward Said’s Orientalism (1993) and Michel Bruneau’s Typology of diaspora and transnationalism (2010) to offer an in-depth analysis of the intricate dynamics involved. The study begins by analysing the function of escapism in the novel, illustrating how the protagonists, Saeed and Nadia, utilize enchanted portals to evade their war-ravaged and oppressive native land. The portrayal of escapism in this context is depicted as a means of survival within the post-colonial diasporic framework, establishing a foundation for a more profound look at identity issues. Examining intimate relationships in the novel delves into the concept of using them as escapism and their importance in navigating periods of identity crisis. The study places significant emphasis on these partnerships symbolic and emotional dimensions, surpassing simply physical interactions. Escapism, in the context of post-colonial diasporic contexts, can be seen as a coping mechanism employed by individuals experiencing identity crises. The Novel Exit West by Mohsin Hamid explores cultural and societal dynamics.